Prenatal auditory stimulation induces physiological stress responses in developing embryos and newly hatched chicks - Hanafi, S. A.; Zulkifli, I.; Ramiah, S. K.; Chung, E. L. T.; Kamil, R.; Awad, E. A. (Elsevier, 2023)
Prenatal stress may evoke considerable physiological consequences on the developing poultry embryos and neonates. The present study aimed to determine prenatal auditory stimulation effects on serum levels of ceruloplasmin (CPN), alpha-1-acid glycoprotein (AGP), corticosterone (CORT), and heat shock protein 70 (Hsp70) regulations in developing chicken embryos and newly hatched chicks. Hatching eggs were subjected to the following auditory treatments; 1) control (no additional sound treatment other than the background sound of the incubator's compressors at 40 dB), 2) noise exposure (eggs were exposed to pre-recorded traffic noise at 90 dB) (NOISE), and 3) music exposure (eggs were exposed to Mozart's Sonata for Two Pianos in D Major, K 488 at 90 dB) (MUSIC). The NOISE and MUSIC treatments were for 20 min/h for 24 h (a total of 8 h/d), starting from embryonic days (ED) 12 to hatching. The MUSIC (1.37 ± 0.1 ng/mL) and NOISE (1.49 ± 0.2 ng/mL) treatments significantly elevated CPN at ED 15 compared to the Control (0.82 ± 0.04 ng/mL) group and post-hatch day 1 (Control, 1.86 ± 0.2 ng/mL; MUSIC, 2.84 ± 0.4 ng/mL; NOISE, 3.04 ± 0.3 ng/mL), AGP at ED 15 (Control, 39.1 ± 7.1 mg/mL; MUSIC, 85.5 ± 12.9 mg/mL; NOISE, 85.4 ± 15.1 mg/mL) and post-hatch day 1 (Control, 20.4 ± 2.2 mg/mL; MUSIC, 30.5 ± 4.7 mg/mL; NOISE, 30.3 ± 1.4 mg/mL). CORT significantly increased at ED 15 in both MUSIC (9.024 ± 1.4 ng/mL) and NOISE (12.15 ± 1.6 ng/mL) compared to the Control (4.39 ± 0.7 ng/mL) group. On the other hand, MUSIC exposed embryos had significantly higher Hsp70 expression than their Control and NOISE counterparts at ED 18 (Control, 12.9 ± 1.2 ng/mL; MUSIC, 129.6 ± 26.4 ng/mL; NOISE, 13.3 ± 2.3 ng/mL) and post-hatch day 1 (Control, 15.2 ± 1.7 ng/mL; MUSIC, 195.5 ± 68.5 ng/mL; NOISE, 13.2 ± 2.7 ng/mL). In conclusion, developing chicken embryos respond to auditory stimulation by altering CPN, AGP, CORT, and Hsp70. The alterations of these analytes could be important in developing embryos and newly hatched chicks to cope with stress attributed to auditory stimulation.